COMPATIBILITY OF WASTE MANAGEMENT PLACES AT TPS3R KSM BAYU SUCI, SUB-DISTRICT MARGA - Devi, Ni Putu Krusita Candra; Trimarianto, Ciptadi (Universitas Ibn Khaldun Bogor, 2022)
The pile of garbage is getting higher and land is starting to be limited at the Mandung TPA in Tabanan Regency to accommodate all the volume of incoming waste. The government's efforts to overcome the waste problem are by implementing independent waste management starting from the village through the TPS3R program. Currently, out of 133 villages in Tabanan Regency, only 11 villages have implemented and have TPS3R. One of the 11 TPS3R is the TPS3R KMS Bayu Suci in Batannyuh Village, Marga District. This study aims to determine the suitability of the capacity of the waste management site at TPS3R KSM Bayu Suci based on the standard of space requirements referring to the Technical Guidelines for the Implementation of Labor-Intensive Activities of the Directorate General of Human Settlements 2020. The importance of this research is to anticipate future problems that arise due to an increase in the volume of waste. but both in terms of processing equipment and land is not sufficient. The results of this study will show the extent and number of ideal equipment needed in maximizing the TPS3R program. The method used in this research is descriptive quantitative method by describing descriptively the data obtained in the field. The main data were obtained from the management of the Bayu Suci KSM and the Tabanan Regency Environmental Service. Based on the results of the study, that the minimum area of land required to maximize the service of TPS3R KSM Bayu Suci is 402 m2 with a minimum composting area of 201 m2. The composting system uses the drum method of 840 units. Based on current conditions, TPS3R KSM Bayu Suci has met the minimum land standard suitability by having a land area of 500m2, but it is still lacking in terms of hangar area for composting area which is only 75 m2 and the need to improve infrastructure to maximize waste processing services.